Metabolomics should be deployed in the identification and characterization of gene‐edited crops. (20th February 2020) - Fraser, Paul D.; Aharoni, Asaph; Hall, Robert D.; Huang, Sanwen; Giovannoni, James J.; Sonnewald, Uwe; Fernie, Alisdair R.
Summary: Gene‐editing techniques are currently revolutionizing biology, allowing far greater precision than previous mutagenic and transgenic approaches. They are becoming applicable to a wide range of plant species and biological processes. Gene editing can rapidly improve a range of crop traits, including disease resistance, abiotic stress tolerance, yield, nutritional quality and additional consumer traits. Unlike transgenic approaches, however, it is not facile to forensically detect gene‐editing events at the molecular level, as no foreign DNA exists in the elite line. These limitations in molecular detection approaches are likely to focus more attention on the products generated from the technology than on the process in itself. Rapid advances in sequencing and genome assembly increasingly facilitate genome sequencing as a means of characterizing new varieties generated by gene‐editing techniques. Nevertheless, subtle edits such as single base changes or small deletions may be difficult to distinguish from normal variation within a genotype. Given these emerging scenarios, downstream 'omics' technologies reflective of edited affects, such as metabolomics, need to be used in a more prominent manner to fully assess compositional changes in novel foodstuffs. To achieve this goal, metabolomics or 'non‐targeted metabolite analysis' needs to make significant advances to deliver greater representation across the metabolome. With the emergence of new edited crop varieties, we advocate: (i) concerted efforts in the advancement of 'omics' technologies, such as metabolomics, and (ii) an effort to redress the use of the technology in the regulatory assessment for metabolically engineered biotech crops. Significance Statement: Unlike with transgenic approaches, it is not facile to detect gene‐editing events forensically at the molecular level, as no foreign DNA exists in gene‐edited lines. The limitation in molecular detection approaches are likely to focus more attention on the products generated from the technology than on the process itself. Here, we highlight the use of metabolomics as a means to characterize (and in some cases identify) gene‐edited material and champion its use for regulatory purposes.